Bite force of patients with tooth pain - Yoshinobu Shoji; Mohd Yusmiaidil Putera Mohd Yusof; Rostam Iffendi Bin Idris; Somsak Mitrirattanakul (Wiley, 2022)
Abstract Objectives The aim of this study was twofold: (i) to measure the bite force of healthy adults and patients with tooth pain and (ii) to evaluate the influence of bite force and age on tooth pain and both genders. It is hypothesized that patients with tooth pain would have lesser bite forces as compared to healthy individuals. Material and Methods Two groups of participants were, the first group comprised 18 healthy adults (9 males, 9 females), while the second group comprised 18 patients with tooth pain (9 males, 9 females), recruited from the Faculty of Dentistry, Universiti Teknologi MARA. Their maximum bite forces were recorded using the Prescale system that consists of pressure‐sensitive films and a precalibrated scanning device. Logistic regression models were used using bite force and age on dichotomous responses of tooth pain status and gender. Results The mean bite force of patients with tooth pain was 684.77 ± 501.13 N, which was lesser than 798.33 ± 492.16 N of the healthy adults. The reduced gender logistic regression model on gender with age was found to be statistically significant (p ≤ .05). Conclusions Even though the mean bite force was smaller in the group with dental pain, this difference was not statistically significant.